Combining Generics, Pre-compilation and Sharing Between Software-Based Processes - Syme, Don; Kennedy, Andrew (2004)
We describe problems that have arisen when combining the proposed design for generics for the Microsoft .NET Common Language Runtime (CLR) with two resource-related features supported by the Microsoft CLR implementation: application domains and pre-compilation. Application domains are “software based processes” and the interaction between application domains and generics stems from the fact that code and descriptors are generated on a pergeneric-instantiation basis, and thus instantiations consume resources which are preferably both shareable and recoverable. Pre-compilation runs at install-time to reduce startup overheads. This interacts with application domain unloading: compilation units may contain shareable generated instantiations. The paper describes these interactions and the diﬀerent approaches that can be used to avoid or ameliorate the problems.